(untitled) (Journal of Economic Research & Business Administration, 2023)
Creative entrepreneurship is an emerging field that has gained increasing attention in recent years. Kazakhstan has seen a surge in small and medium-sized enterprises (SMEs) operating in the creative sector. However, these businesses face numerous challenges that hinder their growth and sustainability. In this paper, we will explore the creative entrepreneurship landscape in Kazakhstan and identify common challenges creative SMEs face. We will also discuss strategies for overcoming these obstacles and achieving success in creative entrepreneurship. Through insights from SMEs in Kazakhstan, we hope to provide valuable guidance for aspiring entrepreneurs and contribute to developing the creative industry in the region. To investigate the challenges entrepreneurs face in Kazakhstan’s creative industries, we obtained data from a sample of 70 small and medium-sized enterprises (SMEs) operating in the sector. Our study aimed to gain insights into the problems encountered by these SMEs to inform policies and strategies for supporting the growth and development of the creative economy in Kazakhstan. Keywords: creative industries, entrepreneurship, business, management